Enhancing Stream Ecosystems Through Riparian Vegetation Management - Jeong-Yun Gu; Jong-Won Lee; Sang-Woo Lee; Yujin Park; Se-Rin Park (Land, 2025)
Land use and land cover changes driven by urbanization and agricultural expansion have increasingly degraded the ecological health of stream ecosystems across watersheds. In Republic of Korea, the Ministry of Environment has designated riparian zones to protect water quality and preserve aquatic ecosystems and continues to implement policies for their management. Given the long-term nature of riparian zone management, providing robust scientific evidence to justify and refine these policies is imperative. In this study, we quantitatively evaluated the role of riparian vegetation on water quality and aquatic ecosystems by using Bayesian Networks. Scenarios were designed to compare the individual effects of riparian vegetation and combined effects of urban and agricultural land use changes. The results indicated that riparian vegetation positively influenced water quality and the benthic macroinvertebrate index at the sub-watershed scale. When riparian vegetation and land use factors were jointly adjusted, scenarios with high riparian vegetation coverage showed improved probabilities of good BMI scores—24.3% under highly agricultural conditions and 27.4% under highly urbanized conditions—highlighting a substantial vegetation effect, particularly in urban areas. This study provides a scientific basis for guiding future riparian restoration and management efforts.